Is the test result correct? A questionnaire study of blood collection practices in primary health care - Söderberg, Johan; Wallin, Olof; Grankvist, Kjell; Brulin, Christine (Journal of evaluation in clinical practice, 2010)
Rationale, aims and objectives  Venous blood tests are important for clinical decision making. Most errors in blood testing are due to human errors before the blood samples reach the laboratory. The present study was designed to investigate venous blood sampling (VBS) practices in primary health care centres (PHCs) compared with clinical laboratory staff. Method  A cross‐sectional survey of 70 PHCs and two clinical laboratories is conducted. All staff responsible for VBS (317 respondents, response rate 94%) completed a questionnaire on VBS practices. Results  Instructions for VBS were not followed in the surveyed PHCs. For example, only 54% reported that they always identified the patient by using name/Swedish identification number and only 5% reported that they always used photo‐ID, the two preferred means for patient identification. Only 12% reported that they always released venous stasis as soon as possible. Fewer PHC staff than clinical laboratory staff reported correct VBS practices. For example, 54% of the PHC staff reported that they always identified the patient by name and Swedish identification number, as compared with 95% of the clinical laboratory staff (P < 0.001). Documented VBS routines and re‐education in VBS were not clearly associated with reported correct VBS practices. Conclusions  In the surveyed PHCs, there are clinically important risks for misidentification of patients and erroneous test results, with consequences for the diagnosis and treatment of patients. Quality interventions, aimed at improving VBS practices, are needed to ensure patient safety.